Peran Orientasi Perbandingan Sosial terhadap Kualitas Hidup Remaja yang Menggunakan Situs Jejaring Sosial Instagram - Jennifer Amanda; Rostiana Rostiana; Bianca Marella (Provitae: Jurnal Psikologi Pendidikan, 2021)
Social comparison is a fundamental cognitive process in an effort to evaluate themselves. Nowadays, social comparison are getting easier to happen especially the frequent use of Instagram. Instagram were known as the most popular social networking sites in Indonesia with more than 60 million active users most of whom are adolescents. However, the active use of Instagram allows people to compare themselves with others (social comparison) which further reduce the quality of life of adolescents. Therefore, this study aims to better understand the relationship between social comparison and quality of life on adolescent while exploring whether the Instagram usage intensity acts a moderator of this relationhsips. Participants in this study are adolescents age 14 to 19 years , live in Jabodetabek and use the Instagram. This study uses several questionnaire includes 25-point WHOQoL-BREF, 10-point intensity social network sites use, and 9-point social media social comparison. The collected data was analysed using Hayes’ PROCESS for SPSS to determine whether Instagram usage intensity was a significant moderator. The results showed that the high intensity use of the social networking site of Instagram moderated the role of social comparison and quality of life with p = 0.00 < 0.05. These results indicate that in the group of adolescents who use Instagram with high intensity, the social comparison predicts a significant decrease in quality of life.